Penetapan kadar fenolik total ekstrak kayu bajakah (Spatholobus littolaris Hassk.) berdasarkan perbedaan konsentrasi etanol dengan metode spektrofotometri Uv-Vis - Indah Triutami Harahap; Anny Sartika Daulay; Fathur Rahman; Haris Munandar Nasution (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The root of the Bajakah tampala (Spatholobus littolaris Hassk.) is one of the plants that is empirically used by the people of the interior of Central Kalimantan as a traditional medicine. According to the preliminary tests conducted, Bajakah Tampala contains phenolics. Phenolic compounds are compounds that have antioxidant activity. The objective of this research was to determine the class of compounds contained in the macerated extract and the total phenolic content and yield of the macerated extract in Bajakah roots. The stages of this research included the processing of plant materials, preparation of macerated and pirated root extracts, characterization examination, phytochemical screening, and the effect on the yield of total phenolic content of Bajakah roots using the UV-Vis spectrophotometry method. The results showed that the simplicia powder of the root of the Bajakah wood contained alkaloids, glycosides, steroids and triterpenoids, flavonoids, phenolics, saponins, and tannins, while the ethanol extract of the roots of the Bajakah wood showed the presence of alkaloids, steroids and triterpenoids, tannins, saponins, flavonoids, and phenolic compounds. The determination of total phenolic content was carried out by determining the maximum wavelength of gallic acid and calculating the total phenolic content based on the difference in ethanol concentration using the UV-Vis spectrophotometry method. The results for determining total phenolic content in 96% ethanol extract were 33.872 ± 0.0420 mg GAE/g, 70% ethanol extract was 29.345 ± 0.2149 mg GAE/g, and 50% ethanol extract was 18.512 ± 0.1355 mg GAE/g. So it can be concluded that the total phenolic content of 96% ethanol extract is higher than that of 70% ethanol extract and 50% ethanol extract.